Biosynthesis, Mode of Action, and Functional Significance of Neurosteroids in the Purkinje Cell - Tsutsui, Kazuyoshi (Frontiers Research Foundation, 2011)
The brain has traditionally been considered to be a target site of peripheral steroid hormones. In addition to this classical concept, we now know that the brain has the capacity to synthesize steroids de novo from cholesterol, the so-called “neurosteroids.” In the middle 1990s, the Purkinje cell, an important cerebellar neuron, was identified as a major site for neurosteroid formation in the brain of mammals and other vertebrates. This discovery has provided the opportunity to understand neuronal neurosteroidogenesis in the brain. In addition, biological actions of neurosteroids are becoming clear by the studies using the Purkinje cell, an excellent cellular model, which is known to play an important role in memory and learning processes. Based on the studies on mammals over the past decade, it is considered that the Purkinje cell actively synthesizes progesterone and estradiol from cholesterol during neonatal life, when cerebellar neuronal circuit formation occurs. Both progesterone and estradiol promote dendritic growth, spinogenesis, and synaptogenesis via each cognate nuclear receptor in the developing Purkinje cell. Such neurosteroid actions mediated by neurotrophic factors may contribute to the formation of cerebellar neuronal circuit during neonatal life. 3α,5α-Tetrahydroprogesterone (allopregnanolone), a progesterone metabolite, is also synthesized in the cerebellum and considered to act as a survival factor of Purkinje cells in the neonate. This review summarizes the current knowledge regarding the biosynthesis, mode of action, and functional significance of neurosteroids in the Purkinje cell during development in terms of synaptic formation of cerebellar neuronal networks.